THE TEACHINGS OF CATUR PIWULANG SUNAN DRAJAT AND FINANCIAL BEHAVIOR IN FOSTERING THE ENTREPRENEURIAL SPIRIT OF SANTRI ALUMNI - Azizah Nurul Hasanah; Suci Yongki Setyowati; Akhmad Sirojudin Munir (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Pesantren have an important role in building the character, ethics, and economic independence of students. Sunan Drajat Islamic Boarding School is famous for combining religious education with entrepreneurship based on the teachings of Catur Piwulang. However, empirical research on how the value of Catur Piwulang and financial behavior affects the formation of entrepreneurial spirit in student alumni is still not widely done. This research aims to examine the relationship between the teachings of Catur Piwulang Sunan Drajat and financial behavior on the entrepreneurial spirit of alumni students. This study uses a mixed method. Quantitative data was collected through a survey of 42 alumni students and analyzed by multiple linear correlations and regression, while qualitative data was obtained from in-depth interviews to strengthen the understanding of the results. The results of the analysis showed that all indicators of Catur Piwulang were positively and meaningfully related to entrepreneurial spirit, with the strongest correlation being the value of spreading affection. However, in the overall regression analysis, the teachings of Catur Piwulang did not have a significant direct influence, while financial behavior was the main factor that predicted the entrepreneurial spirit of alumni. The findings from the qualitative data confirm that the ability to manage finances is a key element of business success, while the value of Catur Piwulang serves as the basis of ethics and entrepreneurial character. This research emphasizes the need to combine the moral values of pesantren and financial ability in the development of pesantren-based entrepreneurship education.